Hydrogeological parameter estimations by partial type curve matching methodology - Sen, Zekai; Dabanli, Ismail; Sisman, Eyup; Guclu, Yavuz Selim (SPRINGER HEIDELBERG, 2015)
During an aquifer test, the depression cone covers various geological formations, and hence, their reflections in time-drawdown data yield noncontinuous scatter of points on double logarithmic paper for type curve matching so as to obtain the aquifer parameters. In this way, transmissivity and storativity parameters are subject to local changes. Although changes are more obvious during the early stages of pumping, as the depression cone expands, the aquifer parameters become more stable, since they represent the average values for the aquifer material under the influence domain of the depression cone. In practice, single type curve matching is sought for the aquifer parameter identification. This paper presents a partial matching for aquifer parameter variation determinations. The application of the methodology is presented for extensive aquifer test data from the Chad Doab area in Pakistan. The partial matching procedure provides a set of aquifer parameter estimations, and the final parameters can be taken as simple as the arithmetic average, but better in the form of weighted average by adapting matching durations as weights. The percentage differences between the classical and partial type curve matching transmissivity (storativity) estimates are about 23 % (40 %). In conclusion, the classical type curve matching procedure yields under estimations in the aquifer parameter values.
Keywords: Aquifer; Matching; Partial; Storativity; Transmissivity; Type curve; FLOW; WELL; Geology